RADIO KOMUNITAS SEBAGAI MEDIA ALTERNATIF UNTUK PEMBERDAYAAN MASYARAKAT - Husni Mubaroq; Ega Fitri Qur’aini (Bajang Institute, 2023)
The purpose of this study is to describe the role of community radio as an alternative medium for empowering local communities. The principle of community media is